Complete Photocatalytic Mineralization of Microplastic on TiO2 Nanoparticle Film - Nabi, Iqra; Bacha, Aziz-Ur-Rahim; Li, Kejian; Cheng, Hanyun; Wang, Tao; Liu, Yangyang; Ajmal, Saira; Yang, Yang; Feng, Yiqing; Zhang, Liwu (iScience, 2020)
Recently, the environmental impacts of microplastics have received extensive attention owing to their accumulation in the environment. However, developing efficient technology for the control and purification of microplastics is still a big challenge. Herein, we investigated the photocatalytic degradation of typical microplastics such as polystyrene (PS) microspheres and polyethylene (PE) over TiO2 nanoparticle films under UV light irradiation. TiO2 nanoparticle film made with Triton X-100 showed complete mineralization (98.40%) of 400-nm PS in 12 h, while degradation for varying sizes of PS was also studied. PE degradation experiment presented a high photodegradation rate after 36 h. CO2 was found as the main end product. The degradation mechanism and intermediates were studied by in situ DRIFTS and HPPI-TOFMS, showing the generation of hydroxyl, carbonyl, and carbon-hydrogen groups during the photodegradation of PS. This study provides a green and cost-efficient strategy for the control of microplastics contamination in the environment. [Display omitted] •Efficient degradation of microplastics under UV light by TiO2 film•Triton-based TiO2 film showed higher photocatalytic performance•The role of radical species during microplastics degradation was elucidated•Degradation mechanism and reaction intermediates were explored Catalysis; Environmental Chemistry; Nanomaterials